Vertical Collaborative Governance in Corporate University Implementation at a Regional Tax Office - Purnomo, Junaedi; Susanti, . (KnE Social Sciences, 2022)
A corporate university is an organization that brings together the learning in an organization and capacity development. The Financial Education and Training Agency (BPPK) in the Financial Education and Training Center (BDK) in Yogyakarta is applying lessons within the relevant regional offices of the Directorate General of Tax (Kanwil DJP) of Jawa Tengah II, specifically with account representative officers in the tax office (KPP). The learning process of a corporate university can be achieved with vertical synchronization and collaborative governance between regional offices. The purposes of a corporate university can be achieved through the optimal and sustainable efforts of the Ministry of Finance. Limitations include: the size of the region’s work, the large number of participants (around 400 persons), the annual period of implementation, and changes in the policy and internal organization of the DJP. Keywords: collaborative governance, corporate university, learning, implementation, limitations